Juvenile ALS with basophilic inclusions is a FUS proteinopathy with FUS mutations. - Bäumer, D; Hilton, D; Paine, S; Turner, M; Lowe, J; Talbot, K; Ansorge, O (2010)
BACKGROUND: Juvenile amyotrophic lateral sclerosis (ALS) with basophilic inclusions is a form of ALS characterized by protein deposits in motor neurons that are morphologically and tinctorially distinct from those of classic sporadic ALS. The nosologic position of this type of ALS in the molecular pathologic and genetic classification of ALS is unknown. METHODS: We identified neuropathologically 4 patients with juvenile ALS with basophilic inclusions and tested the hypothesis that specific RNA binding protein pathology may define this type of ALS. Immunohistochemical findings prompted us to sequence the fused in sarcoma (FUS) gene. RESULTS: Motor symptoms began between ages 17 and 22. Disease progression was rapid without dementia. No family history was identified. Basophilic inclusions were strongly positive for FUS protein but negative for TAR DNA binding protein 43 (TDP-43). Granular and compact FUS deposits were identified in glia and neuronal cytoplasm and nuclei. Ultrastructure of aggregates was in keeping with origin from fragmented rough endoplasmic reticulum. Sequencing of all 15 exons of the FUS gene in 3 patients revealed a novel deletion mutation (c.1554_1557delACAG) in 1 individual and the c.1574C>T (P525L) mutation in 2 others. CONCLUSION: Juvenile ALS with basophilic inclusions is a FUS proteinopathy and should be classified as ALS-FUS. The FUS c.1574C>T (P525L) and c.1554_1557delACAG mutations are associated with this distinct phenotype. The molecular genetic relationship with frontotemporal lobar degeneration with FUS pathology remains to be clarified.